Implementasi Gugatan Legal Standing dan Class Action dalam Praktik Peradilan di Indonesia - Bambang Sutiyoso (Jurnal Hukum IUS QUIA IUSTUM, 2004)
The implementation of group representative accusation especially for legal standing in the practice of judge in Indonesia is still faced with the handicaps procedural technically. The regulation of legislation is still restricted in law material, while in formal law (the court of justice) is not regulated clearly. The uncertain of procedure informal law (the court ofjustice) in its regulation is really not the handicaps for thejudge for taking thejust decision, because the judge can apply the other law resource. Although, it has been issued PERMA No. 1 the year 2002 that regulate the group representative accusation, for the next it should be formulated strictly in the new Justice Court of Code Procedures. The group representative accusation is the moresimple justice alternative, quick and lowcost.